2014
DOI: 10.1007/s12126-014-9213-z
|View full text |Cite
|
Sign up to set email alerts
|

Situational Analysis of the Impact of GNI on the Elderly Population

Abstract: The national income and other general socio-economic factors are strong determinants of population health and the increasing elderly population. In countries where resources are less, people are much less healthy than people living in rich countries. In wealthier countries that have made immense progress in health indicators, the resulting change in age structure and morbidity and mortality patterns portends even greater financial demands on the health sector. This study noted the trends in life expectancy ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…One of the mechanisms leading to health inequalities in adulthood Koivusilta et al found was the interplay between behaviors and educational pathways in adolescence. Jalal and Khan (2014) noted that there is improvement in life expectancy with increasing gross national income (GNI) per capita and GDP because where there are fewer resources, people are much less healthy than those living in rich countries. Fedeli's (2014) results show that health expenditure for the long and short-term provides an empirical support for the existence of Wagner's law.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms leading to health inequalities in adulthood Koivusilta et al found was the interplay between behaviors and educational pathways in adolescence. Jalal and Khan (2014) noted that there is improvement in life expectancy with increasing gross national income (GNI) per capita and GDP because where there are fewer resources, people are much less healthy than those living in rich countries. Fedeli's (2014) results show that health expenditure for the long and short-term provides an empirical support for the existence of Wagner's law.…”
Section: Introductionmentioning
confidence: 99%